lAS INTERACCIoNES DE loS ESTUDIANTES EN ENToRNoS VIRTUAlES DE APRENDIZAJE: HERRAMIENTAS INFoRMÁTICAS PARA SU SEGUIMIENTo Y DIRECCIÓN - Castillo Maza, Juan Victoriano (2010)
Have tools to guide, monitor and assess the interactions of students in virtual forums to sing learning is essential to support real learning process. This paper aims to provide two tools with which manages to make the content analysis of the interactions and student performance in the forum of the virtual learning environment (called the ten emoticons), and another that provides a graphical representation of structural diagrams, both the model of student interaction and group that is active in the forum of the virtual learning environment (VLE). The application of the instrument and the computer tool helps the teacher supervise, guide and evaluate the process of learning and training and development in the EVA group.